Craft beer production in Río Azul Brewing - Terrón Hernández, D; Del Río Pérez , E; Ibeas , JI (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2021)
Craft beers are getting more significant in the beer market, and being a plausible alternative versus the industrial beers during the last 40 years all over the world. Thus the demand of the craft beer is getting higher each year in Europe and USA since 1980. A good control for the brewing process is essential to maintain quality and consistency in this new industry. The focus of this research is to study and analyze how the brewing process is occurring in a Sevillian brewing factory and to control their progress by measuring the pH and gravity of the wort during every step of maceration and boiling. We have also analyze the variation of the beer density and so the alcohol, along the fermentation, for every specific kind of beer. This research involves the study of four different craft beers, Imperial Stout, Season IPA, Blonde and NEIPA. Although the research is not entirely completed, we have observed that each beer shows a typical evolution referred to the pH or density measurement during production. First we found that the initial values for pH and gravity in the wort are not always the same for the same type of beer, what’s means that the process is not completely reproducible. Nevertheless, the parameters, both for the initial and the final product, remains always between the correct parameters to produce high quality beers. We have also observed that even during bottling, variations can be detected, making each batch particular, probably because storing condition of the beer before bottling or the CO2 control during this process. Conclusions: A high level of control is required in the craft beer factories to get a product of quality and consistency, what is claimed by the consumers